Construction of s-extremal optimal unimodular lattices in dimension 52. Issue 2 (2nd April 2020) - Harada, Masaaki
Abstract : An s -extremal optimal unimodular lattice in dimension 52 is constructed for the first time. This lattice is constructed from a certain self-dual F 5 -code by Construction A. In addition, as neighbours of the lattice, two more s -extremal optimal unimodular lattices are constructed.